The effect of red, blue, green and white light emitting diodes on pigment content and sugar accumulation in wheatgrass - Witoon Yindeesuk; Sirichai Sartpan; Surachart Kamondilok (My University, 2021)
Abstract This research studied the effect of light-emitting diode (LED) on pigment content and sugar accumulation in wheatgrass. The wheatgrass was cultured under different lighting conditions, consisting of white (W), red (R, 660 nm), blue (B, 480 nm), and green (G, 525 nm) LEDs. The daily light integral is 2.33 mol/day in 7 days. The wheatgrass was cultured in a close system at a temperature of 25±1 °C and humidity of 75 ± 3 %. In the experiment, the completely randomized design was used with three replications of 100 seedings. The wheatgrass that was grown under red and blue light with ratio 1:1 yield a chlorophyll A of 1.0363 mg/L, chlorophyll B of 0.4189 mg/L, and carotenoid of 0.3208 mg/L. The sugar accumulation of 8.234 mg/L is a maximum under the red, green, and blue treatment with statistical significance.
Keywords: Photosynthetic pigment; Light effects on plants